Assange must answer. - Davis, Jema (New Internationalist, 2016)
A letter to the editor is presented in response to the article published in the previous issue, featuring an interview with computer programmer Julian Assange that leaves out critical information about the reasons for his ongoing presence in the Ecuadorian embassy in London, England.